Does the side of middle cerebral artery compromise matters in the mortality after thrombolysis in ischemic stroke? - Renata Dal-Prá Ducci; Marcos Christiano Lange; Carla Heloísa Moro; Rodrigo Harger; Alexandre Luiz Longo; Norberto Luiz Cabral; Francisco Manoel Branco Germiniani; Edison Matos Nóvak; Viviane de Hiroki Flumignan Zétola (Arquivos de Neuro-Psiquiatria)
The impact of the side in middle cerebral artery (MCA) ischemic stroke is not well established. Our aim was to analyze the differences between right (RMCA) and left middle cerebral artery (LMCA) stroke in patients submitted to intravenous thrombolysis and the influence of the affected side in the patient’s mortality after 3 months. Method Patients with MCA ischemic stroke submitted to intravenous thrombolysis from March 2010 to December 2011 at two Brazilian Stroke Centers were included. Differences between patients with RMCA and LMCA stroke were identified by univariate analysis. Results Forty-five patients with RMCA stroke and 67 with LMCA stroke were analyzed. Patients with LMCA had a higher incidence of atrial fibrillation (p = 0.031), although patients with RMCA more often had a previous ischemic stroke (p = 0.034). The mortality over 3 months was similar for either side (OR = 1.20 ;0.37 - 4.29, p = 0.772). Conclusion The side of the MCA ischemic stroke did not influence the patients mortality.